2018
DOI: 10.1128/jvi.00805-18
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus E1A Activation Domain Regulates H3 Acetylation Affecting Varied Steps in Transcription at Different Viral Promoters

Abstract: Despite a wealth of data associating promoter and enhancer region histone N-terminal tail lysine acetylation with transcriptional activity, there are relatively few examples of studies that establish causation between these histone posttranslational modifications and transcription. While hypoacetylation of histone H3 lysines 18 and 27 is associated with repression, the step(s) in the overall process of transcription that is blocked at a hypoacetylated promoter is not clearly established in most instances. Stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
46
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(51 citation statements)
references
References 52 publications
5
46
0
Order By: Relevance
“…Although SAHA treatment did not appear to cause a change in acetylation status of H3 or H4 in the E1A/hexon coding regions we examined (Fig. 5), loss of HDAC2 activity could affect acetylation at the promoter regions or transcriptional start sites of the early and late genes, since H3 acetylation was observed at HAdV-2 early promoters (34). Interestingly, knockdown of the histone acetyltransferase Tip60 and reduced H4 acetylation actually resulted in increased HAdV-5 E1A promoter activity (63).…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Although SAHA treatment did not appear to cause a change in acetylation status of H3 or H4 in the E1A/hexon coding regions we examined (Fig. 5), loss of HDAC2 activity could affect acetylation at the promoter regions or transcriptional start sites of the early and late genes, since H3 acetylation was observed at HAdV-2 early promoters (34). Interestingly, knockdown of the histone acetyltransferase Tip60 and reduced H4 acetylation actually resulted in increased HAdV-5 E1A promoter activity (63).…”
Section: Discussionmentioning
confidence: 79%
“…Like several other DNA viruses and retroviruses (e.g., herpes simplex virus, Kaposi's sarcoma-associated herpesvirus, simian virus 40, and murine leukemia virus), the HAdV DNA associates with cellular histones during specific stages of the virus life cycle (60)(61)(62). Modifications of these histones has very recently been shown to modulate HAdV gene expression (34), but many questions regarding the "chromatinization" and epigenetic regulation of the HAdV genome still remain unanswered. The cellular proteins and chromatin-remodeling enzymes involved in mediating these processes have yet to be identified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As with E4, this may reflect a difference in how this promoter is regulated distinctly from the early promoters (36). Alternatively, it is possible that other histone modifications drive expression from the MLP or E4 promoter; for example, p300 drives E1A CR3-mediated acetylation of K18 and K27 in histone H3 (14), which we did not investigate in this study. The deletion of residues 13 to 15 within E1A is in close proximity to a region that binds pCAF (37); a recent study (38) has shown that E1A fragment consisting of residues 1 to 33 binds to the pCAF catalytic site and inhibits its acetyltransferase activity.…”
Section: Discussionmentioning
confidence: 98%
“…Essentially, E1A243R can sequester away p300/CBP from CR3, leading to reduced transactivation (13). A recent study has confirmed that two areas flanking the CR3 are capable of binding to p300/CBP, resulting in altered histone H3 acetylation at lysines (K) 18 and 27 (14). Studies have also shown that E1A is capable of tethering itself to cell-bound transcriptional repressors, which brings the powerful CR3 transactivation domain to repressed promoters, forcing expression of genes that they regulate (15,16).…”
mentioning
confidence: 99%